Pro Visual Studio 2005 Team System - Levinson, Jeff; Nelson, David (Apress : Imprint: Apress, 2006)
It is clear that Visual Studio Team System (VSTS) is the future of development from Microsoft's perspective. We agree. Development is no longer a personal pursuit by one developer in a darkened room; it is a collective effort by a team of peers. VSTS supports this broader vision by providing a complete collaboration platform for the entire project team. VSTS takes a services-oriented approach leveraging Windows Sharepoint Services and SQL Server Business Intelligence Suite. Additionally, VSTS brings the lifecycle to life by making it part of the integrated suite. This book will guide you through the entire breadth of VSTS. If you are a stakeholder, you have a portal that gives you instant access to project documents, status, and performance indicators. If you are primarily a project manager, you will learn how create, manage, and assess the team performance. As VSTS is integrated with Microsoft Office, you can quickly assign tasks and gather work status. With reporting from the data warehouse you get real-time view of all project metrics. If you are a developer, you will learn how to write higher-quality code, ensure that the code works, and that it performs well. For those seeking to use test-driven development, VSTS is the tool for you. If you're an architect, there is a new set of domain-specific modeling tools that makes it easy to visualize systems, determine application relationships, and deploy into a logical datacenter. For testers, Microsoft's new suite of test tools provides a powerful web testing environment with virtually unlimited extensibility. In addition, the new load tools allow you to perform world-class scalability testing. Even if you are just considering adopting VSTS, you will be provided with a comprehensive overview. Further, you will be able to deep-dive into any area with detailed descriptions, samples and walk-throughs. Roll up your sleeves and get ready for a new way of developing solutions!